THE PRESIDENT’S AUTHORITY IN THE APPOINTMENT, TRANSFER, AND DISMISSAL OF CIVIL SERVANTS IN DEMOCRACY IN INDONESIA - M. Najibur Rohman (Journal Philosophy of Law, 2021)
The purpose of writing this article is to analyze the president’s authority in the appointment, transfer, and dismissal of Civil Servants after the issuance of Government Regulation Number 17 of 2020 concerning Amendments to Government Regulation Number 11 of 2017 concerning Management of Civil Servants. In this latest policy, the president is stated to withdraw the delegation of authority if the bureaucracy is not run based on a system of merit and professionalism. This policy has sparked debate because the change is seen as an attempt to dominate and hegemony of the government over the bureaucracy through the creation of undemocratic laws. There are fears that the bureaucracy will become a political tool that will keep it from its primary public servant goal. This research is part of normative legal research (normative research) or doctrinal legal research with a statutory, case, and conceptual approach. The study findings show that constitutionally the president’s authority to withdraw the delegation of authority in the appointment, transfer, and dismissal of civil servants has indeed been based on the provisions of the law where the president is the holder of government power. Still, with this regulatory change, presidential power has become more dominant. It opens up opportunities for conflict of interest to intensify in the administration of the bureaucracy so that it is not in line with democratic values.